Effects of Stimulus Presentation Level on Stop Consonant Identification in Normal-Hearing and Hearing-Impaired Listeners - Plyler, Patrick N.; Hedrick, Mark S. (Journal of the American Academy of Audiology, 2002)
The purpose of the present study was to determine whether varying the presentation level of stop consonant stimuli resulted in similar phonetic boundary shifts for listeners with normal and impaired hearing. Sixteen normal-hearing and 16 hearing-impaired listeners categorized synthetic speech stimuli as /b/, /d/, or /g/. The onset frequency of F2 varied from 900 to 2300 Hz (100-Hz steps), and the presentation level varied from 92 to 62 dB SPL (10-dB steps) for each stimulus presentation. Hearing-impaired listeners had significantly more missing boundary values than normal-hearing listeners; however, the correlation between the number of missing boundary values and hearing sensitivity was not significant. Comparison of boundary shift with level demonstrated that hearing-impaired listeners had a smaller boundary shift with increasing level than normal-hearing listeners. The amount of boundary shift was not correlated with audibility. The results of the current study suggest that increasing the presentation level of a signal does not result in performance similar to that of listeners with normal hearing.
Keywords: Hearing loss; phonetic boundary; speech perception; stop consonant identification